(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper employs Michel Foucault’s theory of heterotopia to examine brothels as paradoxical spaces of both isolation and penetration in Elif Shafak’s 10 Minutes 38 Seconds in This Strange World. Foucault’s heterotopias are spaces that exist outside conventional societal norms—distinct, marginalized zones that often serve as sites of exclusion or alternative social practices. These spaces, marked by their detachment from the dominant social order, facilitate mechanisms of isolation and penetration, both physical and symbolic. Defined by their deviance from the expected, they are viewed by state and capital as occupying “wrong” locations, moving in “wrong” directions, or fostering “wrong” relationships. While much of the scholarship on heterotopias has focused on public institutions such as prisons, hospitals, and cemeteries, this paper shifts the lens to brothels, spaces that, despite their marginalization, play a critical role in the disenfranchisement and exploitation of women in literature. In 10 minutes 38 Seconds in this Strange World, the brothel emerges as a heterotopic site where cultural norms are both inverted and reinforced. Leila, the protagonist, is forcibly confined to this space—a confinement dictated by male coercion and societal neglect. The brothel thus functions dually: it isolates women within its walls, while granting men access to dominate and penetrate, symbolically and physically, through those very boundaries. By applying Foucault’s theory of heterotopia to Shafak’s portrayal of the brothel, this paper reveals the complex dynamics of isolation, othering, and exploitation that pervade such spaces. It argues that the brothel, as a heterotopic site, serves not only as a mirror of societal power structures but also as a space that actively contributes to the reinforcement of those structures. Through this lens, the paper offers a nuanced exploration of the intersection between gender, spatiality, and societal norms, illuminating the ways in which physical spaces reflect and sustain power dynamics.